Kajian Fitokimia Ekstrak Metanol Daun Belimbing Wuluh (Averrhoa bilimbi L.) Asal Kecamatan Koto Tangah - Serli, Salsabilla Putri; Riga, Riga; Nasra, Edi (Lembaga Yasin AlSys, 2024)
Secondary metabolites are compounds synthesized by plants, microbes, or animals through biosynthesis that are used to support life. The content of secondary metabolites in plants is often used as traditional medicine. In this research, samples of wuluh starfruit leaves (Averrhoa blimbi L.) were used as traditional medicine to treat coughs, diabetes, and others. The purpose of this study is to determine the secondary metabolite content in wuluh starfruit leaves (A. Blimbi L.) in Koto Tengah district through maceration, phytochemical, and thin layer chromatography methods. This research was carried out through a sample preparation process, maceration using methanol as a solvent, phytochemical tests to test the content of alkaloids, flavonoids, saponins, and polyphenols/tannins by looking at the color change in the sample, and confirmation through thin layer chromatography by looking at the color and Rf value. The secondary metabolite test revealed that belimbing wuluh leaves were positive for tannins, flavonoids, alkaloids, and saponins.